Two innovative prototypes for collecting pruning biomass: Early performance tests and assessment of the work quality. (October 2018) - Pari, L.; Suardi, A.; Frąckowak, P.; Adamczyk, F.; Szaroleta, M.; Santangelo, E.; Bergonzoli, S.; Del Giudice, A.; Dyjakon, A.
Abstract: The growing demand for biomass for energy use has led equipment manufacturers to focus their attention on the management of pruning wastes and on finding solutions for recovering such a huge amount of biomass. The first attempt consisted of adapting mulchers, which were used to incorporate these wastes into the soil; interest later shifted towards chippers and balers, which were able to produce a high-grade fuel. Two innovative prototypes for pruning waste collection were developed within the EuroPruning Project: a baler (PRB 1.75) designed by PIMR research institute (Poland), and a chipper (PC50) designed by the machine manufacturer ONG s. n.c. (Italy) with the scientific support of the CREA-IT institute (Italy). The main goal was to design special machines to harvest multiple types of pruning wastes from permanent crops and to build a sustainable and cost-effective supply chain. Both prototypes showed encouraging results. Their performances were largely comparable with those reported for similar machines, showing values of losses ranging from 36.2 to 46.2% and a maximum productivity of 2.80 (PC50) and 3.03 tfm h −1 (PRB1.75). Moreover, the particle size distribution in the feedstock produced by the chipper PC50 complies with the international standard for the commercial category P45. This study reports on the performance of both prototypes and the quality of the product obtained during the preliminary harvest-pruning tests carried out in vineyards and in peach and apple orchards. Highlights: An unsuitable mechanization may slow down the complete exploitation of pruning. A baler and a chipper were developed to improve the marketability of the hog fuel. The baler allowed to collect and compact apple pruning up to 3.3 t ha −1 . The double-auger mounting blades of the chipper performs a sharp cut of the wood. The particle size of grape and peach woodchips produced by the PC50 complied with the request of stakeholders.